Synthesis of silica and silicon from rice husk feedstock: A review - Ibrahim Hamidu; Benjamin Afotey; Bright Kwakye-Awuah; Daniel Adjah Anang (Heliyon, 2025)
A lot of attention has been drawn to environmentally friendly and sustainable materials in the need to decarbonize the planet. The utilization of agro-waste to meet this need has increased in recent times. Among the various agro-wastes, rice husk has gained more traction due to its abundance, unique constituents, and properties suitable for advanced material synthesis. Precursor materials such as silica and silicon used in advanced materials synthesis are also synthesized from rice husk. The synthesis of these advanced materials depends on the rice husk pretreatment and thermochemical conversion approach. Pretreatment methods such as acid leaching generally yield higher silica purity compared to water leaching. However, the use of acid in leaching impurities during pretreatment leads to the release of harmful chemicals. Among thermochemical methods used in silica synthesis, the hydrothermal method has gained more attention due to the use of water as a liquid medium and the elimination of the raw materials drying step, reducing emissions and energy demand in the process. Metallothermic reduction methods such as magnesiothermic and aluminothermic reduction of silica to silicon have attracted much attention due to their low reduction temperature. This review discusses the composition and properties of rice husk and its thermochemical conversion to silica (SiO2) and silicon (Si). Silica and silicon are essential materials used as framework or precursor materials in the synthesis of other advanced materials such as zeolites and catalyst supports. The second part of the review discusses the various thermochemical conversion approaches and their kinetics. The final part of the review discusses the various rice husk-derived advanced materials and their applications.